Penerapan Terapi Menghardik Halusinasi Terhadap Pasien Eks Psikotik dalam Rehabilitasi Sosial - Na’imatun Nuroniyyah Yulia Saputri; Muslihudin Muslihudin (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
Along with the rapid development, modernization and industrialization efforts, social changes and problems are growing. So that people who are unable to make adjustments, can experience mental turmoil, mental disorders and even mental disorders called psychotics. Therefore, this study aims to describe the application of hallucinatory rebuke therapy in the rehabilitation process of ex-psychotic patients at the Dosarso Shelter House, Kebumen. This research method uses a type of qualitative research with a case study approach. This study had 4 subjects, namely 2 ex-psychotic patients who were still experiencing hallucinations, 1 nurse and 1 administrator who worked at the Dosaraso Shelter in Kebumen. The results of this research show that rebuke therapy at the Dosaraso Shelter Home in Kebumen is carried out in groups and individually. The social rehabilitation service model provided by Dosaraso includes the Institutional Based Rehabilitation (IBR) service model. Then the type of psychotic experienced by TS patients is schizophrenic functional psychotic with auditory and visual hallucinations, while patient D is paranoid functional psychotic with auditory hallucinations. This rebuke therapy is carried out through several stages, namely starting from preparing the place, explaining the therapy, agreeing to the therapy, time contract, implementation, and finally asking the patient's feelings. This research can also help counselors in carrying out therapeutic steps for ex-psychotic patients so that it is very helpful in overcoming social problems in society.